The epigean and subterranean pseudoscorpions of the genus Roncus from Sicily, with description of new species (Pseudoscorpiones: Neobisiidae) - Gardini, Giulio; Gardini, Pietro (Zootaxa, 2026)
A taxonomic revision of the epigean and subterranean species of Roncus L. Koch, 1873 from Sicily is proposed and a key is provided that also includes the two subterranean species of the genus from Malta (Roncus melitensis Gardini & Rizzerio, 1987) and Tunisia (Roncus comasi Mahnert, 1985). The following new species are described: Roncus bavierai sp. nov. (♂♀, loc. typ.: Palermo Province, Piana degli Albanesi, Grotta del Garrone 160 Si/PA), Roncus gallettiae sp. nov. (♂♀, loc. typ.: Ragusa Province, Ragusa, Dolina di Galermi 6020 Si/RG), Roncus hyblaeus sp. nov. (♂♀, loc. typ.: Syracuse Province, Melilli, Grotta Villasmundo 7032 Si/SR), Roncus magrinii sp. nov. (♂♀, loc. typ.: Trapani Province, Custonaci, Grotta della Clava 8073 Si/TP) and Roncus nicolosii sp. nov. (♂♀, loc. typ.: Syracuse Province, Syracuse, Grotta del Conzo 7005 Si/SR). The following new subjective synonymy is proposed: Roncus carusoi Gardini & Rizzerio, 1987 syn. nov. of Roncus siculus Beier, 1963.